2005
DOI: 10.17221/5607-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on koi herpesvirus (KHV) - a review

Abstract: ABSTRACT:The first outbreaks of a disease connected with high mortality of common carp and koi carp caused by koi herpesvirus (KHV) were reported in 1998 in Israel and in the United States. Since then, several cases have been confirmed all over the world. At present, this viral disease is considered to be one of the most risky factors affecting populations of common carp and koi carp. Affected fish become disoriented and swim erratically with high breathing frequency, swollen gills and partially local skin les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 18 publications
1
61
0
2
Order By: Relevance
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…The virus survives at low temperature but disease outbreaks occur at 17-28°C. No morbidities have been reported at 13 and 30°C [48]. The disease progression is very fast in summer and slow in winter [46].…”
Section: Koi Herpes Virusmentioning
confidence: 94%
“…After the first report of this disease in Israel, it has been reported in US and many other Asian and European countries [27,40,45,47,53,54]. This disease has been reported form Indonesia, Japan, Taiwan, Israel, Malaysia, Thailand, Singapore, Philippines, Hong Kong and Korea [1,48]. The infected fish show signs of erratic swimming behaviour, disorientation, gasping at the surface and high mortality.…”
Section: Koi Herpes Virusmentioning
confidence: 99%
“…This disease was initially reported in 1998 in Israel and USA, where the outbreaks resulted in high mortality of koi and common carp (Cyprinus carpio) (Pokorova et al 2005).…”
mentioning
confidence: 99%